2018
DOI: 10.21649/akemu.v24i1.2305
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Sex by Cheiloscopy as an Aid to Establish Personal Identity

Abstract: Background: Establishment of individuality is the basic concept of the humanity, which formulates personal identity. Forensic medicine is basically the science of identification and during last few decades multiple research work has been conducted for detection of different methods of identification to establish a baseline of identity e.g. dental data, fingerprinting, DNA analysis, anthropometry, identification of sex, assessment of age, determination of height and blood groups identification. Among these, DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our results also match those observed in earlier studies done in Lahore, Pakistan. 8,9,15 The probable reason for the same results is due to same environmental conditions, genetic makeup and ethnicity. 7 However, our results are in contrast to the studies done in Nigeria, 12 Iran, 16 Egypt 17 & few states of India.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Our results also match those observed in earlier studies done in Lahore, Pakistan. 8,9,15 The probable reason for the same results is due to same environmental conditions, genetic makeup and ethnicity. 7 However, our results are in contrast to the studies done in Nigeria, 12 Iran, 16 Egypt 17 & few states of India.…”
Section: Discussionmentioning
confidence: 91%
“…Our results also support the findings of previous researches which were done in Lahore division (Central Punjab), Pakistan. 8,9,15 So this can be inferred that factors like geographical location, ethnicity, and environmental conditions can influence the final outcome. Unfortunately, no studies are done in other regions of Punjab, Pakistan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four researchers studied only middle part of lip prints of Indian population (size samples were less than 400) and the dominant lip prints were type I, III and IV (Kinra et al 2014;Multani et al 2014;Remya et al 2016;Verghese et al 2010). Researchers from Pakistan and India used whole lips for their studies, with sample size of less than 400 and the dominant lip print patterns were type I and IV (Ishaq et al 2018;Kautilya et al 2013;Kumar et al 2016). A lot of other researchers analysed 4 quadrants of lips in order to determine the dominant pattern in Indian population and the results showed that type I, I', II, III and V were among the dominant patterns (Bindal et al 2009;Gondivkar et al 2009;Kapoor & Badiye 2017;Nagrale et al 2014;Prabhu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ishaq et al 2018;Kautilya et al 2013;Kumar et al 2016) and even only the middle part of the lips(Kinra et al 2014;Multani et al 2014;Remya et al 2016). Only Wan Rafiuddin (Wan Rafiuddin et al 2018) used 6 sections, similar to the current study.…”
mentioning
confidence: 99%